Bureaucracy Reform and Good Governance Implementation Challenge in Indonesia - Selpiah Sappe (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2019)
This research aims to describe and analyze the problems give the solutions for theimplementation of the bureaucracy reform of good governance in Indonesia. Thisresearch uses the method of basic research with the type of research literature thatexamines various theories such as books, journals, newspapers and rules related tobureaucratic reform in achieving good governance. The results showed that there aresome problems faced by the government in the implementation of good governancethrough bureaucratic reform policy. Some of the problems the inability of thebureaucracy in adapting to the dynamics of the community; high political interventionagainst the bureaucracy; public doubt on the effectiveness of policies, which areplanned and implemented by the bureaucracy. The authors provide solutions that is thereform of the organization (structural); capacitation reform; and reform ofinstrumentation.